2016
DOI: 10.1016/j.psychres.2016.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of co-morbid attention-deficit and hyperactivity disorder on cognitive function in male children with Tourette syndrome: A controlled study

Abstract: Tourette syndrome (TS) and attention-deficit and hyperactivity disorder (ADHD) are co-morbid neurodevelopmental conditions affecting more commonly male patients. We set out to determine the impact of co-morbid ADHD on cognitive function in male children with TS by conducting a controlled study. Participants included four matched groups of unmedicated children (age range 6-15 years): TS (n=13), TS+ADHD (n=8), ADHD (n=39), healthy controls (n=66). Following clinical assessment, each participant completed a batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…However, normal performance has been reported on the Corsi span [ 92 ], the Benton visual retention test [ 92 ], the delayed matching to sample task [ 67 ], the self-ordered pointing task [ 92 ], and the finger windows (a subtest of the wide range assessment of memory and learning) [ 61 ]. Comorbid ADHD could lead to some deficits here again, since Termine et al [ 87 ] found impaired forward and backward Corsi span in TS + ADHD but not in TS-only children.…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, normal performance has been reported on the Corsi span [ 92 ], the Benton visual retention test [ 92 ], the delayed matching to sample task [ 67 ], the self-ordered pointing task [ 92 ], and the finger windows (a subtest of the wide range assessment of memory and learning) [ 61 ]. Comorbid ADHD could lead to some deficits here again, since Termine et al [ 87 ] found impaired forward and backward Corsi span in TS + ADHD but not in TS-only children.…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 82%
“…In children and adolescents with TS, good verbal working memory was often reported, as proven by normal forward and backward digit span [ 61 , 86 , 87 ] and good n -back performance [ 88 ]. The presence of ADHD could impair working memory capacities, since worse forward and backward digit span was found in TS + ADHD children, when compared to TS children without comorbidities [ 89 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
“…Second, altered flexibility was found in adults with OCD 12 (but not in children 13 ) and in TS, 15 but not in TTM 93,95,[97][98][99] (except in one study, which found a deficit in the Object Alternation task, but not in the Wisconsin Card Sorting Test [WCST] 100 ). Attention deficits are found in all three disorders, 12,101 but more mixed results are found in TS (some studies found a deficit, [102][103][104] whereas others did not [105][106][107] ). However, one must keep in mind that attention deficit/hyperactivity disorder (ADHD) is a frequent comorbidity in TS and that the attention deficit results mentioned above seem linked only to comorbid ADHD.…”
Section: Neuropsychologymentioning
confidence: 95%
“…Durch Faktorenanalyse in epidemiologischen Studien mit GTS-Patienten hat sich gezeigt, dass Patienten mit GTS + ADHS eine höhere Wahrscheinlichkeit für einen früheren Krankheitsbeginn, weitere psychiatrische Komorbiditäten und damit eine höhere Krankheitsschwere haben. Darüber hinaus geht das GTS + ADHS im Vergleich zu GTS ohne ADHS mit mehr kognitiven Störungen wie dysexekutiven Defiziten einher [30].…”
Section: Komorbiditätenunclassified